1994
DOI: 10.1161/01.atv.14.3.460
|View full text |Cite
|
Sign up to set email alerts
|

Effects of age, lipoproteins, and hemostatic parameters on the role of homocyst(e)inemia as a cardiovascular risk factor in men.

Abstract: Previous studies have identified moderately elevated plasma concentrations of homocyst(e)ine as an independent risk factor for coronary heart disease (CHD). The atherogenicity of homocyst(e)ine has mostly been attributed to its effects on endothelial cells, platelets, and the hemostatic system. In this case-control study of 199 male CHD patients and 156 age-matched control subjects, we analyzed the role of homocyst(e)ine as a cardiovascular risk marker in the context of traditional risk factors as well as of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
1
1

Year Published

1995
1995
2002
2002

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(46 citation statements)
references
References 29 publications
1
43
1
1
Order By: Relevance
“…Studies of the von Willebrand factor and fibrinogen (important vascular determinants of increased platelet aggregation and secretion that may be involved in the development of thrombosis) also favor the theory of platelet hyperactivity. Indeed, plasma homocysteine concentration was correlated with plasma fibrinogen in hyperhomocysteinemic patients with coronary heart disease (von Eckardstein et al, 1994). Furthermore, an increased plasma von Willebrand factor is found in hyperhomocysteinemic subjects bearing premature arterial disease (Freyburger et al, 1997) and, of major relevance, acute methionine loading induced moderate hyperhomocysteinemia results in a significant increase in von Willebrand factor (Constant et al, 1999).…”
Section: Alterations Of Vascular Thromboresistancementioning
confidence: 95%
See 2 more Smart Citations
“…Studies of the von Willebrand factor and fibrinogen (important vascular determinants of increased platelet aggregation and secretion that may be involved in the development of thrombosis) also favor the theory of platelet hyperactivity. Indeed, plasma homocysteine concentration was correlated with plasma fibrinogen in hyperhomocysteinemic patients with coronary heart disease (von Eckardstein et al, 1994). Furthermore, an increased plasma von Willebrand factor is found in hyperhomocysteinemic subjects bearing premature arterial disease (Freyburger et al, 1997) and, of major relevance, acute methionine loading induced moderate hyperhomocysteinemia results in a significant increase in von Willebrand factor (Constant et al, 1999).…”
Section: Alterations Of Vascular Thromboresistancementioning
confidence: 95%
“…The results of cross-sectional studies of subclinical vascular disease show that higher homocysteine concentrations are associated with greater carotid artery intimal-medial wall thickness Selhub et al, 1995;Willinek et al, 2000). It has also been reported that homocysteine level is related to the extent of atherosclerosis in coronary and peripheral arteries (Chao et al, 1999b;van den Berg et al, 1996;Verhoef et al, 1997b;von Eckardstein et al, 1994). Third, as we will detail below (see "Potential Pathogenic Mechanisms of Hyperhomocysteinemia"), our own work (Durand et al, 1997a) and the work of Lentz et al (1996) and Bellamy et al (1998) give experimental evidence that moderate hyperhomocysteinemia, which leads to vascular dysfunction, might increase the cardiovascular risk independently of other risk factors.…”
Section: Hyperhomocysteinemia: An Expected Causal Risk Factor For Athmentioning
confidence: 97%
See 1 more Smart Citation
“…Some medications, such as niacin, methotrexate, and phenytoin, may also increase homocysteine levels [20][21][22][23] . Ethnic differences have been reported to interfere with the homocysteine levels, which are lower in black individuals as compared with Caucasian and Asian individuals [24][25][26][27][28][29][30][31][32][33] .…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 30 studies have compared the homocysteine levels of patients with coronary artery disease and those of control groups with no disease 27,28 . Patients with coronary artery disease had significantly higher fasting plasma homocysteine levels in 22 out of 27 studies 29,30 with a risk ratio of 1.2 to 10.9 after adjusting for other risk factors.…”
Section: Discussionmentioning
confidence: 99%